2011
DOI: 10.1177/1052562910397501
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Safe Environment for Women’s Leadership Transformation

Abstract: This study used qualitative data to describe how transformational learning was achieved in a women-only training (WOT) program. The article argues that an environment conducive to transformational learning for women was created from the harmonious coalescing of the presence of all-women participants and instructors with gender-sensitive teaching and learning practices. The integration of these elements created safety and participant willingness to break with habitual patterns. This article contributes to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 35 publications
4
96
0
Order By: Relevance
“…Developmental relationships, such as those with mentors and coaches, provide psychosocial support and career development advice (Kram, 1985). Since women learn well through others’ stories of success and struggle (Debebe, 2011), women-only leadership development programs have been recommended (Debebe et al, 2016), especially for populations lacking critical mass such as women in leadership and women in STEM disciplines. Furthermore, peer coaching provides a safe environment for developmental feedback to be exchanged and mutual learning to occur (Parker et al, 2014).…”
Section: Developing Women Who Persist and Succeedmentioning
confidence: 99%
“…Developmental relationships, such as those with mentors and coaches, provide psychosocial support and career development advice (Kram, 1985). Since women learn well through others’ stories of success and struggle (Debebe, 2011), women-only leadership development programs have been recommended (Debebe et al, 2016), especially for populations lacking critical mass such as women in leadership and women in STEM disciplines. Furthermore, peer coaching provides a safe environment for developmental feedback to be exchanged and mutual learning to occur (Parker et al, 2014).…”
Section: Developing Women Who Persist and Succeedmentioning
confidence: 99%
“…With four children she cared for herself was not an excuse for IndriaNur, S.Ag.,M.Pd.I to keep silent. IndriaNur was still able to manage her time so that she became Chairwoman of the Department of Tarbiyah in State Islamic College(STAIN) ofSorong.Women's leadership is considered effective in the world of education because women have accuracy in doing work (Stead, V. and Elliott, C., 2013).With leadership skills, she previously even occupied the position of secretary majors for the duration of four years of service.In the period of leadership as the secretary of the department, students have the opportunity to communicate directly with the secretary of the department.They get guidance to navigate the endless academic life.In fact, the presence of secretary of department and figure of womanwas able to provide maximum support for the achievement of student ability in completing the study.Generally, women have the ability and have met the requirements to become a leader, but most of them are not confident and feel inferior to compete with men (Chabaya, O., Rembe, S. and Wadesango, N., 2009).Also, (Debebe, G., 2011) Argued that, in one guidance of Community Service Program (KKN), IndriaNur was even asked as a model lecturer.Women's leadership has a positive effect on student achievement in education. In addition, there is no relationship between women's leadership and available employment opportunities ( Beaman, L., Duflo, E., Pande, R. and Topalova, P., 2012.…”
Section: Women and Educationmentioning
confidence: 99%
“…Several scholars have argued in favor of women-only sessions. For example, Debebe (2011) suggested that such sessions confer a sense of belonging, provide social validation, and are conducive to transformational learning for women by creating an atmosphere of psychological safety. Ely et al (2011: 486) further argue that women-only programs "go beyond teaching women what they need to know and do; they also support women in understanding and shaping who they are and can become."…”
Section: Practical Implicationsmentioning
confidence: 99%